Return on Assets Bank Pembangunan Daerah di Pulau Jawa: Studi pada Efisiensi sebagai Determinan - Novia Muplihah; Dadang Hermawan; Destian Arshad Darulmalshah Tamara (Indonesian Journal of Economics and Management, 2022)
This study aims to analyze the effect of Non Performing Loan (NPL) and Operating Income Operating Expenses (BOPO) on Return On Assets (ROA) at Regional Development Banks in Java for the period 2011-2020. This title was chosen because during 2020 BPD has not been efficient in disbursing funds because it does not apply the principles of prudence and bank efficiency so that non-performing loans increase. The research method used is associative research with a quantitative method approach. The sampling technique uses a saturated sample so that the total population and sample are the same, namely five Regional Development Banks on the island of Java for the 2011-2020 period. Data processing was carried out using the IBM SPPS Statistics 25 application. The results of the study stated that partially NPL had no effect on ROA, while BOPO had a negative effect on ROA. Meanwhile, simultaneously NPL and BOPO affect ROA.